ANALYSIS OF NURSING CARE IN NSTEMI PATIENTS WITH THE APPLICATION OF DEEP BREATHING RELAXATION AND MURATTAL THERAPY TO OVERCOME THE PROBLEM OF ACUTE PAIN - Kartika Milaningrum; Nur Ainiyah; Umdatus Soleha; Firdaus (Nurse and Holistic Care)
Introduction: Non-ST Elevation Myocardial Infarction is usually caused by severe narrowing of the coronary arteries, this can cause chest pain that can last long and intense, cold sweat, nausea and vomiting, and feeling as if you are facing death.